Editorial - v.9, n.1, jul./dez. 2011 - Gildenir Carolino Santos; Danielle Thiago Ferreira (RDBCI: Revista Digital de Biblioteconomia e Ciência da Informação, 2011)
Editorial - v.9, n.1, jul./dez. 2011